Health-related quality of life, fear of recurrence, and emotional distress in patients treated for thyroid cancer. Issue 7 (September 2017) - Rogers, S.N.; Mepani, V.; Jackson, S.; Lowe, D.
Abstract: Diagnosis of differentiated thyroid carcinoma (papillary or follicular) and its treatment may be associated with a poor health-related quality of life (HRQoL), and with fear of recurrence (FoR), and distress. To our knowledge, this is the first time a single FoR screening question (written to complement a HRQoL questionnaire), has been reported with HRQoL and levels of distress in patients treated for the disease. In April 2014 we did a cross-sectional survey of patients who had presented to the Merseyside and Cheshire thyroid cancer network between April 2009 and November 2013. Questionnaires comprised the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30, the THYCA-QoL, the Emotion Thermometers, and the new FoR screening item. A total of 249 surveys were sent and 169 patients responded (68%). The most prevalent issues included tiredness, problems with sleep and needing to rest, pain (particularly in muscles and joints), a dry mouth, hot flushes and tolerating heat, gaining weight, and feeling slowed down or weak; also, having trouble taking long walks or doing strenuous activities, feeling tense, worried, irritable, and anxious, and having difficulty remembering things. One in seven patients (95% CI 9% to 21%) responded to the single FoR question that they "had a lot of fears of recurrence that really preoccupied their thoughts" or were "fearful all the time that their cancer might return and that they struggled with this". Distress overall was relatively low. In conclusion, the HRQoL issues reported by these patients were different from those reported by patients with other cancers of the head and neck. It would be helpful to identify FoR in a subgroup of patients with differentiated thyroid cancer so that they could be given additional support.